Education and Tax Policies in the Presence of Informality - Anna-Mariia Tkhir (ZBW - Leibniz Information Centre for Economics, 2021)
I study the effect of refugees' protection status on labor market outcomes focusing on a recent cohort of Syrian and Iraqi refugees entering Germany between 2013 and 2016. My empirical analysis exploits a sudden and unpredictable change in the assessment of the Federal Agency responsible for asylum claims to grant full refugee status in accordance with the Geneva convention to refugees from these two countries in March 2016. Using data from the IAB-BAMF-SOEP survey of refugees and exploiting the policy change in a fuzzy regression discontinuity design, estimation results indicate a substantial negative effect of subsidiary protection status on earnings and employment. This paper analyzes the aggregate long-run effects of education and tax policies in the presence of a large informal sector. I develop an overlapping-generation life-cycle model with heterogeneous agents and incomplete markets, where agents make educational and occupational choices. Education is costly but ensures a wage premium in the future. Education costs are partially subsidized by the government. Individuals choose to operate either in the formal or in the informal sector given that the education premium is higher in the former. However, formal workers must pay progressive income taxes. I calibrate my model to Brazil and assess the effects of education subsidies on the overall economy. The increase in the education subsidy improves educational attainment, expands formalization, and increases welfare. The subsidy rate which covers 100% of education costs maximizes welfare leading to the overall welfare gain of around 94% measured in consumption equivalent variation. Due to a significant positive effect on the tax base, the education subsidy is self-financing in the long run. Tax schedule reforms have mild effects on the aggregate measures of education. However, they alter the educational composition of labor. Reducing the level of income tax or flattening the tax schedule leads to the reallocation of highly educated and productive individuals into the formal sector.
Keywords: I24; E26; J24; 330; Human Capital; Informal Economy; Education Policy; Tax Policy